Co-administration of oral killed whole-cell recombinant cholera toxin B-subunit vaccine (WC-rCTB) and live Salmonella Typhi Ty21a vaccine: a prospective randomized open-label trial - Riekkinen, Marianna; Terrinoni, Manuela; Pakkanen, Sari H.; Kaim, Joanna; Vahlberg, Tero; Lundgren, Anna; Kantele, Anu (Oxford University Press, 2026)
Background
Cholera and typhoid fever are often co-endemic, making vaccine co-administration practical. However, due to lack of immunogenicity data, current guidelines advise against co-administration of the oral inactivated whole-cell recombinant cholera toxin B-subunit vaccine (WC-rCTB) and the oral live Salmonella Typhi Ty21a vaccine.
Methods
Healthy adults (18–65 years) were randomized 1:1:1 to receive WC-rCTB with Ty21a (group Ch + Ty), WC-rCTB alone (group Ch) or Ty21a alone (group Ty). Peripheral blood mononuclear cells (PBMCs) were isolated on Days 0, 5 and 7 from all, plus on Days 12 and 14 from WC-rCTB recipients, to assess antibody-secreting cells (ASCs) specific to rCTB and to typhoidal O9,12-structures by enzyme-linked immunosorbent spot (ELISPOT) assay. Vibriocidal antibodies were assessed, and anti-rCTB IgA/IgG and anti-S. Typhi lipopolysaccharide (LPS) IgA/IgG/IgM were measured by enzyme-linked immunosorbent assay (ELISA) in Day 0 and 28 ± 3 serum samples. Adverse events (AEs) were recorded during one month.
Results
The final study population included 63 volunteers, 21 per group. A non-significant trend towards stronger rCTB-specific ASC (IgA + IgG + IgM) peak responses was observed in group Ch + Ty compared to group Ch (geometric mean, GM 94 vs 32 ASC/106 PBMC, P = 0.096). Serum anti-rCTB IgA and IgG fold rises (post-vaccination vs pre-vaccination) were higher in group Ch + Ty than in group Ch (IgA P = 0.039, IgG P = 0.028), whereas vibriocidal fold rises were comparable between the two groups (P = 0.847). ASC (IgA + IgG + IgM) peak responses to typhoidal O9,12-structures were comparable between groups Ch + Ty and Ty (GM 183 vs. 210 ASC/106 PBMC, P = 0.684). Serum anti-S. Typhi LPS IgA, IgG and IgM fold rises were also similar across Ch + Ty and Ty groups (all P-values ≥0.145). AEs were comparable in single and co-administration groups.
Conclusions
Co-administration of the oral cholera and typhoid vaccines demonstrated favourable safety and robust immunogenicity for both vaccines, supporting their simultaneous use without spacing precautions.